International Brethren conference on missions ; 4 - Gasque, W. Ward; International Brethren conference on Missions Singapore July 1993 (1993)
Contents : tape 4 : "Missions and Africa : Nigeria, Tanzania, Zaire, Zambia"; "Communicating the Gospel"/Ward Gasque
Keywords: Brethren movement -- missions -- congresses